THU0461 Comparison between clinical profile and outcome of patients with juvenile onset and adult onset takayasu arteritis. (12th June 2018) - Goel, R.A; Danda, D.; Joseph, G.; Nair, A.; Ravindran, R.; Jeyaseelan, V.
Abstract : Background: There is a paucity of data comparing juvenile onset Takayasu arteritis (jTA) and adult onset TA (aTA). Objectives: We aimed to compare differences in clinical profile and outcome of patients with jTA and aTA attending our centre during 1998–2017. Methods: Details of demography, clinical presentation, laboratory results, angiography and treatment response were collected prospectively for 252 and retrospectively for the rest of patients with TA. Disease activity was defined by Indian Takayasu Activity Score- A (ITAS-A)(CRP). 1 Complete remission (CR) was defined as ITAS-A=0 with no angiographic progression. Patients with onset of disease at ≤16 years of age were classified as jTA while the rest as aTA. Results: Among 602 patients with TA during this period, 119 (19.8%) were jTA, while 483 were aTA. Female predominance was less striking in jTA (71.4%) than aTA (79%), p=0.047. Patients with jTA had presented more commonly with fever (29% vs 17.4%, p=0.002), headache (31% vs 18%, p=0.002), pain abdomen (11% vs 5.6%, p=0.031), systolic hypertension (66.4% vs 48.4%, p<0.001), cardiomyopathy (15.1% vs 5.4%, p<0.001) and raised creatinine (16% vs 4.7%, p<0.001) while claudication as presenting symptom was less common in jTA (39%) as compared to aTA (55%), p=0.003. Pulse abnormality tended to be commoner in aTA. Angiographically, type-I disease (5.1% vs 22.6%, p<0.001) and coronary involvement (8.3% vs 20.6%, p=0.016) was less common while type-IV disease occurred more frequently (25% vs 14.3%, p=0.004) in jTA than in aTA. Logistic regression showed similar results after adjustment for gender. Median ITAS 2010 score was higher in jTA [7 (2–14)] than aTA [5 (2–11)]. Follow up was available for 77 and 287 patients with jTA and aTA respectively. Median follow up duration was 32 10–61 months for jTA and 27 10–59 months for aTA. CR was attained more frequently in jTA (n=67; 87%) than aTA (n=190; 66.2%), p=0.001. Another, 7 (9%) and 55 (19.2%) of patients with jTA and aTA respectively achieved partial response with immunosuppression. Among patients with initial CR, relapse of active disease during further follow up was observed more frequently in jTA [n=20, (29.9%)] as compared to aTA [n=50, (26.6%)], p=0.029. Altogether, persistently stable disease course was more common in jTA (62.3%) than aTA (47.5%), p=0.029. Conclusions: In our large cohort of TA treated with uniform immunosuppression protocol, systemic features, hypertension, cardiomyopathy, renal dysfunction and type IV disease are more commonly observed in jTA while claudication, pulse abnormality, coronary involvement and type I disease are more frequent in aTA. Patients with jTA respond better to immunosuppression but relapse more frequently than aTA. Persistent stable disease course is commoner in jTA patients. Reference: [1] Ruchika Goel, Debashish Danda, et al. Long term outcome of 251 patients with Takayasu Arteritis on combination immunosuppressant therapy: single centre experience from a large tertiary care teaching hospital in southern India. Seminars in Arthritis and Rheumatism, http://dx.doi.org/10.1016/j.semarthrit.2017.09.014 Disclosure of Interest: None declared